1998
DOI: 10.1007/s005340050027
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignancies of the hepato-biliary-pancreatic system in organ allograft recipients

Abstract: A biloma is a rare abnormal accumulation of intrahepatic or extrahepatic bile caused by a traumatic or spontaneous rupture of the biliary tree. The reported incidence of postoperative biloma ranges from 4.8% to 7.6%. Biliary drainage is usually important and necessary for the treatment of biloma, but sometimes bile leakage fails to improve despite prolonged conservative drainage. We report a case of postoperative refractory biliary leakage managed with percuta-neous ablation by N-butyl cyanoacrylate. (Korean J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The cumulative number of years of follow-up is also unknown, and this makes it difficult to calculate the actuarial risk. 2,6,[19][20][21] In this respect, data from single centers with long-term follow-up have become an important source of information for the incidence and nature of de novo cancers, which can then be compared with surveillance epidemiological end results data. Furthermore, these data can be presented as a standard incident ratio (SIR).…”
Section: See Article On Page 1428mentioning
confidence: 99%
“…The cumulative number of years of follow-up is also unknown, and this makes it difficult to calculate the actuarial risk. 2,6,[19][20][21] In this respect, data from single centers with long-term follow-up have become an important source of information for the incidence and nature of de novo cancers, which can then be compared with surveillance epidemiological end results data. Furthermore, these data can be presented as a standard incident ratio (SIR).…”
Section: See Article On Page 1428mentioning
confidence: 99%
“…Previous studies showed that the incidence of HCC after kidney transplant is much higher in Asian countries where HBV infection is endemic, when compared with the Western countries. 9,10 However, prophylactic use of antiviral therapy may theoretically suppress the HBV DNA levels and reduce the risk of HCC. 11 In fact, there are only limited data in literature regarding the development and management of HCC after kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Although immunosuppression is mandatory to prevent graft rejection, the development of de novo malignancies in the long-term course after transplantation is a wellknown risk. 14,15 In our patient, the immunosuppression was composed of a triple combination with steroids, cyclosporine A, and MMF. Organ transplant recipients have a 3-to 4-fold increased incidence of malignancies compared with the incidence in the general population.…”
Section: Discussionmentioning
confidence: 97%